2018
DOI: 10.1128/aem.01832-18
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Anaerobic Methanotroph “ Candidatus Methanoperedens nitroreducens” to Oxygen Stress

Abstract: ABSTRACT“CandidatusMethanoperedens nitroreducens” is an archaeon that couples the anaerobic oxidation of methane to nitrate reduction. In natural and man-made ecosystems, this archaeon is often found at oxic-anoxic interfaces where nitrate, the product of aerobic nitrification, cooccurs with methane produced by methanogens. As such, populations of “Ca. Methanoperedens nitroreducens” could be prone to regular oxygen exposure. Here, we investigated the effect of 5% (vol/vol) oxygen exposure in batch activity ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 102 publications
2
35
0
Order By: Relevance
“…Analysis of the microbial community in the Italian paddy field ANME-2d enrichment using a bioreactor approach has been described by Guerrero-Cruz et al . 2018. Metagenome sequencing of the DNA derived from this bioreactor revealed that 83% of 16S rRNA gene reads were assigned to Ca .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Analysis of the microbial community in the Italian paddy field ANME-2d enrichment using a bioreactor approach has been described by Guerrero-Cruz et al . 2018. Metagenome sequencing of the DNA derived from this bioreactor revealed that 83% of 16S rRNA gene reads were assigned to Ca .…”
Section: Resultsmentioning
confidence: 95%
“…Growth conditions and operation of the bioreactor containing ANME-2d archaea enriched from an Italian paddy field soil are described by Guerrero-Cruz et al . (2018). Sampled material from both reactors was centrifuged (10000 × g , 20 min, 4°C) and pellets were kept at −80°C until subsequent freeze-drying and following lipid and isotope analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Candidatus Methanoperedens, mediating nitrate-dependent anaerobic CH 4 oxidation, was also typically representative of these oxygen-rich environments, although it was found to be relatively more abundant within the deeper sampling depth. This genus can counteract oxidative damage and adapt in environments where it is regularly exposed to oxygen [52].…”
Section: 32methane Oxidizing Microorganismsmentioning
confidence: 99%
“…Furthermore, ‘ Ca . Methanoperedens’ might be more sensitive to oxygen exposure (Guerrero-Cruz et al 2018 ) than anammox and ‘ Ca . Methylomirabilis’ bacteria (Luesken et al 2011a , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methylomirabilis’ as well as anammox is dependent on nitrite. Oxygen is detrimental for all three processes (Strous et al 1999b ; Luesken et al 2012 ; Guerrero-Cruz et al 2018 ). Although several studies have enriched combinations of N-damo bacteria and archaea or N-damo archaea and anammox bacteria, few studies have been designed to enrich all three groups from the same source material (Arshad et al 2017 ; Stultiens et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%